Can subnational accounting give an early warning of fiscal risks? - Irwin, Tim (OECD Publishing, 2020)
The early detection of state and local fiscal problems can help in resolving them quickly before they turn into crises. Early detection should be easier if subnational governments prepare high-quality accounts. A survey and case studies were therefore undertaken to investigate the nature of subnational accounting in OECD and key partner countries, as well as the use of subnational accounts by national governments that monitor subnational finances. The results show that in many countries subnational accounting has characteristics that should help in the early detection of fiscal problems, including the use of accrual accounts prepared according to largely harmonised standards. Many national governments use a wide range of indicators from the accounts to monitor the financial health of subnational governments. However, there is room for progress including in the monitoring of non-financial assets and reporting of currently off-balance sheet liabilities